1989
DOI: 10.1523/jneurosci.09-01-00280.1989
|View full text |Cite
|
Sign up to set email alerts
|

Responses of lateral geniculate neurons that survive long-term visual cortex damage in kittens and adult cats

Abstract: Damage to visual cortex (areas 17-19) in kittens or adult cats produces severe retrograde degeneration of neurons in the dorsal lateral geniculate nucleus (LGN). However, some neurons survive in otherwise degenerated portions of the LGN after a visual cortex lesion at any age. Previous studies have shown that there are well-defined differences in potential retinal inputs, soma size, synaptic connections, outputs, and physiological properties of output targets of the surviving LGN cells in cats that received vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 54 publications
1
15
1
Order By: Relevance
“…Neurophysiologic studies have shown that binocular suppression begins as early as dLGN. 43 – 46 From modeling work, Ding and Levi 47 suggested that the interocular inhibition in the LGN, which lacks of orientation selectivity, could provide the neurophysiologic substrate for the interocular gain-control in binocular combination. This would predict that an imbalance of interocular inhibition at dLGN can affect SED combo .…”
Section: Discussionmentioning
confidence: 99%
“…Neurophysiologic studies have shown that binocular suppression begins as early as dLGN. 43 – 46 From modeling work, Ding and Levi 47 suggested that the interocular inhibition in the LGN, which lacks of orientation selectivity, could provide the neurophysiologic substrate for the interocular gain-control in binocular combination. This would predict that an imbalance of interocular inhibition at dLGN can affect SED combo .…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the nondominant inhibition of the LGN cells remains uncertain. It could conceivably be due to direct inhibitory interaction between right-eye and left-eye laminae of the LGN, via inhibitory interneurons (Guillery, 1966 ), which is supported by the fact that the visual cortex removal does not reduce nondominant influences on LGN cells (Pape & Eysel, 1986 ; Sanderson et al, 1971 ; Singer, 1970 ; Tumosa, McCall, Guido, & Spear, 1989 ). However, Ding and Sperling ( 2006 , 2007 ) found that, although essentially orientation independent, the interocular gain control was somewhat more effective for vertical and horizontal gratings than diagonal ones, which suggests that some of the gain control is likely of cortical origin, i.e., arises beyond the LGN, because the LGN cells are essentially indifferent to orientation.…”
Section: Discussionmentioning
confidence: 99%
“…This circuitry is normally formed and maintained through neuronal activity (Shatz, 1996). Even in adult animals, dLGN neurons are capable of eliciting plastic changes in their morphology and connectivity, as revealed by experiments where the dLGN target in the cortex is severely damaged (Tumosa et al, 1989).…”
Section: Possible Involvement Of Occ1-related Proteins In the Maturedmentioning
confidence: 99%